Gcm counteracts Toll-induced inflammation and impacts hemocyte number through cholinergic signaling - Bazzi, Wael; Monticelli, Sara; Delaporte, Claude; Riet, Céline; Giangrande, Angela; Cattenoz, Pierre B. (Frontiers in Immunology, 2023)
Hemocytes, the myeloid-like immune cells of Drosophila, fulfil a variety of functions that are not completely understood, ranging from phagocytosis to transduction of inflammatory signals. We here show that downregulating the hemocyte-specific Glide/Gcm transcription factor enhances the inflammatory response to the constitutive activation of the Toll pathway. This correlates with lower levels of glutathione S transferase, suggesting an implication of Glide/Gcm in ROS signaling and calling for a widespread anti-inflammatory potential of Glide/Gcm. In addition, our data We showreveal the expression of neurotransmitter acetylcholine receptors in hemocytes and that Toll activation affects their expressions, disclosing a novel aspect of the inflammatory response mediated by neurotransmitters. Finally, we provide evidence for acetylcholine receptor nAchRalpha6 regulating hemocyte proliferation in a cell autonomous fashion and for Finally, we provide evidence for acetylcholine receptor nAchRalpha6 regulating hemocyte proliferationnon-cell autonomous cholinergic signaling regulating the number of hemocytes. Altogether, this study provides new insights on the molecular pathways involved in the inflammatory response.